(untitled) (International Journal of Innovative Technologies in Economy, 2024)
This study aims to determine the effect of financial ratios and assets on stock prices with exchange rates as moderating variables. In this study, the variables used are Return On Asset (ROA), Earning Per Share (EPS), and Fixed Asset Value. The data used in this study are secondary data from the IDX and the company’s annual report. The population used in this study are consumer good industry sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The analysis technique is the MRA (Moderated Regression Analysis) test using SPSS software version 29. The results showed that EPS, Fixed Assets and Exchange Rates affect stock prices, while ROA does not affect stock prices. The moderating variable test in this study shows that Exchange Rate can moderate EPS.